2020
DOI: 10.3389/fbioe.2020.00952
|View full text |Cite
|
Sign up to set email alerts
|

The Few Who Made It: Commercially and Clinically Successful Innovative Bone Grafts

Abstract: Bone reconstruction techniques are mainly based on the use of tissue grafts and artificial scaffolds. The former presents well-known limitations, such as restricted graft availability and donor site morbidity, while the latter commonly results in poor graft integration and fixation in the bone, which leads to the unbalanced distribution of loads, impaired bone formation, increased pain perception, and risk of fracture, ultimately leading to recurrent surgeries. In the past decade, research efforts have been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 86 publications
1
53
0
1
Order By: Relevance
“…Recent studies have revealed varying results which cast doubt on whether the additional use of PRP with other grafting materials in the treatment of infrabony defects and sinus augmentation provides any added benefits [ 89 , 177 , 179 , 180 , 181 ]. Since the early 2000s, BMP-2 and BMP-7 have been the most commonly used USFDA approved growth factors for bone grafting procedures in dentistry and function as the active components of two major commercial products— Infuse TM and Osigraft TM , respectively [ 182 ]. However, the production of Osigraft TM has since been halted and the use of Infuse TM has been associated with a large number of life-threatening complications [ 182 ].…”
Section: Classification Of Dental Bone Graft and Substitute Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have revealed varying results which cast doubt on whether the additional use of PRP with other grafting materials in the treatment of infrabony defects and sinus augmentation provides any added benefits [ 89 , 177 , 179 , 180 , 181 ]. Since the early 2000s, BMP-2 and BMP-7 have been the most commonly used USFDA approved growth factors for bone grafting procedures in dentistry and function as the active components of two major commercial products— Infuse TM and Osigraft TM , respectively [ 182 ]. However, the production of Osigraft TM has since been halted and the use of Infuse TM has been associated with a large number of life-threatening complications [ 182 ].…”
Section: Classification Of Dental Bone Graft and Substitute Materialsmentioning
confidence: 99%
“…Since the early 2000s, BMP-2 and BMP-7 have been the most commonly used USFDA approved growth factors for bone grafting procedures in dentistry and function as the active components of two major commercial products— Infuse TM and Osigraft TM , respectively [ 182 ]. However, the production of Osigraft TM has since been halted and the use of Infuse TM has been associated with a large number of life-threatening complications [ 182 ]. Although the use of GFBSs has presented a promising area for the introduction of new bone substitutes, novel bioactivated products with GFs have generally not progressed beyond the animal study stage in recent years.…”
Section: Classification Of Dental Bone Graft and Substitute Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that SmartBone ® is also available as a new CE-labeled class III medical device, and it has a vast clinical record being also commercially available as a bone substitute for bone regenerative surgeries in all skeletal districts for oral, maxillofacial, orthopedic, and oncologic indications [ 11 , 12 , 13 , 14 ]. This allows the current developments to have a robust path into translating research from bench to bed and to market finally [ 15 ].…”
Section: Introductionmentioning
confidence: 99%